The Implementation Of Weekly Conversation Program (Muhadatsah) To Improve The Daily Speaking Ability "At Darut Taqwa Bungkal Ponorogo" - Marilin, Firdausia Lysdiana; Ahmadi, Ahmadi (Al-Wazan: Journal of Arabic Education, 2024)
Speaking plays an important role in social interaction with others to obtain or exchange information because speaking is one way to express feelings, ideas, experiences, and knowledge to others. As well as the position of English in Darut Taqwa Islamic Boarding School is a mandatory language in daily communication. This condition requires Darut Taqwa Islamic Boarding School to prepare efforts to support the students' language learning process. Therefore, Darut Taqwa Islamic Boarding School established a program, namely Weekly Conversation (Muhadatsah) to teach students speaking skills directly and actively daily in the dormitory environment. Speaking skills need to be taught because speaking is one of the basic skills that someone in learning a foreign language must master. The objectives of this study are to 1) Describe the Weekly Conversation Program (Muhadatsah): objectives, materials, learning organization, learning experiences, strategies, and evaluation, implemented to improve daily speaking ability at Darut Taqwa Islamic Boarding School for girls. 2) Describe the obstacle students face in the Weekly Conversation Program (Muhadatsah). This research was designed using a qualitative method with a case study design. Data were collected through observation, interview, and documentation. Data were analyzed using Miles and Huberman with data reduction, data display, and conclusions. The results showed that 1) Implementation of the Weekly Conversation Program (Muhadatsah) to improve the daily speaking ability at the Darut Taqwa Islamic boarding school for girls, which there are elements: Objectives, Materials, Learning Organization, Learning Experience, Strategy, and Evaluation. 2) Obstacles faced by students in the Weekly Conversation Program (Muhadatsah).